A microcomputer application for managing information used when weaning patients from mechanical ventilation. - Barton DM; Burns SM; Fahey SA (Computers in Nursing)
This article describes a microcomputer application designed to manage data collected from patients assessed for weaning from mechanical ventilation. The application has menu options for obtaining individual summaries of serial weaning assessments. These summaries provide an overview of patients' progress during the weaning process. Users also have the option of obtaining information about procedures and problems often encountered during weaning. In addition, weaning summary data are easily transferred to mainframe computers for statistical analyses. The application is an efficient data manager and provides information that can be used during the patient care decision process, for staff and student instruction, and for research purposes.